OPTIMIZAREA ÎNVĂŢĂMÂNTULUI ÎN REPUBLICA MOLDOVA - USM ADMIN (Moldova State University, 2007)
The article deals with the problem of modernization and optimization of the structure of pre-university education in Republic of Moldova. It provides some information about the training of teachers in Higher Educational Institutions and the attitude of society towards the teacher's occupation.